Evolution pathways of robotic technologies and applications in construction. (January 2022) - Chang, Siwei; Francis Siu, Ming-Fung; Li, Heng; Luo, Xiaowei
Abstract: Recent research has focused on developing new automated construction robots. However, the evolution pathways of robotics technologies and their specific applications are yet to be explored analytically. This study aimed to trace these evolution pathways using critical juncture timings to describe them. First, data were collected from the literature using a two-step literature selection method. Robotic technologies and application terms were then extracted and labelled using natural language processing techniques. Next, the probability of the selected terms was calculated as importance weighting. Finally, the critical junctures were identified by clustering the weightings using the k -means clustering algorithm. The proposed method revealed three critical junctures, thereby identifying four development stages since 1983. It was found that the needs for construction robots emerged after 2015. The robot configuration evolved from large-scale machinery to smaller and movable vehicles. Image-related sensor systems and processing algorithms, such as 3D cameras and deep learning algorithms, have become popular after 2009. These improvements allow for more accurate operation in unknown and complex environments. Inspection works may be the golden chance to further advance robot implementation.